MEMBIARKAN DIRI DIPIMPIN OLEH ROH Pengantar Studi Literer Atas Surat Paulus Kepada Jemaat Di Roma (8,1-27) - Yoakim R. Ndelo (P3TK, Sanata Dharma University, 2013)
Gods act in Jesus Christ underlies the whole development of Pauls theology, particularly in his letter to the Romans, since it is the center of historical salvation, in which the past and the future are seen in a new approach. The cross, death and resurrection of Christ are the fulfilment of Old Testament prophecy, as well as the basis for anticipating eschatological salvation, and it makes Christ become son of God. The Christians, in their existence in Christ, while letting themself to be lead by the Holy Spirit, also participate in divine sonship, and through adoption as sons allowed to call God their Father. The Holy Spirit, then, becomes the key point of the new reality of the believers. The Holy Spirit leads them and, as much as their acceptance to the Holy Spirit, they will take part in new reality of Christ.